Epidermal permeability barrier function and sphingolipid content in the skin of sphingomyelin synthase 2 deficient mice. Issue 8 (13th February 2018) - Nomoto, Koji; Itaya, Yurina; Watanabe, Ken; Yamashita, Tadashi; Okazaki, Toshiro; Tokudome, Yoshihiro
Abstract: Sphingomyelin synthase (SMS) is an enzyme that generates sphingomyelin (SM) from ceramide (CER) and phosphatidylcholine. SM in the epidermis is a precursor of CER, an important lipid for epidermal permeability barrier function. However, the physiological role of SMS in skin is unclear. To uncover the function of SMS in skin, we investigated sphingolipid metabolism enzyme activity in skin, SM content in the epidermis, CER content in the stratum corneum (SC) and transepidermal water loss (TEWL) as an indicator of barrier function in SMS2‐knockout (KO) mice. The activities of sphingolipid metabolism enzymes in skin homogenates were measured using a fluorescently labelled substrate. Enzymatic reaction products were detected by high‐performance liquid chromatography (HPLC). Lipids in the epidermis or SC were extracted and quantified by high‐performance thin layer chromatography (HPTLC). TEWL was measured using a Tewameter TM300. In SMS2‐KO mice, SMS activity in skin homogenates, epidermal SM content and SC CER content were significantly decreased relative to wild‐type (WT) mice. The TEWL of SMS2‐KO mice was significantly increased compared to WT mice. Our data indicate that SMS2 generates SM in the epidermis and contributes to epidermal permeability barrier function and will support understanding of SM‐related metabolic disorders.